Modulation of auditory sensory memory by chronic clinical pain and acute experimental pain: a mismatch negativity study. Issue 1 (December 2018) - Fan, Lu; Sun, Ya-Bin; Sun, Ze-Kun; Wang, Ning; Luo, Fei; Yu, Feng; Wang, Jin-Yan
Abstract Pain, especially chronic pain, can lead to cognitive deficits. Mismatch negativity (MMN) is a change-specific component of the auditory event-related brain potential (ERP) that is thought to provide a unique window into sensory memory processes. The present study was designed to determine how chronic and acute pain affects auditory sensory memory. In experiment 1, MMNs elicited by standard and deviant auditory stimuli at short and long inter-stimulus intervals (ISIs) were compared between trigeminal neuralgia (TN) patients and demographically matched healthy controls (HCs). The TN patients were found to have stronger attenuation of the MMN at longer ISIs than HCs. Correlation analysis revealed a significant positive correlation between the sensory subscale of McGill Pain Questionnaire and MMN amplitude reduction across ISI conditions. In experiment 2, MMNs recorded before, during, and after the cold pressor test were compared in healthy subjects. MMN amplitude was significantly reduced during pain exposure and recovered immediately thereafter. These results suggest that both chronic pain and acute pain can interfere with automatic change detection processes in the brain. This study provides the first evidence that chronic pain patients have a faster auditory memory trace decay than HCs.